A new microscopic coordinated deformation model of Ti-based bulk metallic composites during tensile deformation. (November 2019) - Li, Liyuan; Li, Jinshan; He, Yixuan; Lai, Minjie; Zhu, Mingxiang; Wang, William Yi; Kou, Hongchao; Wang, Jun
Abstract: In this paper, a new coordinated deformation mode of 'pull apart' has been evidenced by analyzing a series of microscopic deformation steps of Ti48 Zr20 Nb12 Cu5 Be15 metallic glass composite after tensile fracture. Different from the two previously found deformation modes of 'tensile' and 'shear', this mode is characterized by the irregular but completely fitted deformation steps between the two dendritic fragments which are separated by the tortuous matrix. This model describes the coordinated deformation behavior of dendrites and matrix in the microscopic plastic flow process and can be used to interpret the good balance of strength and ductility of metallic glass composites. Graphical abstract: Unlabelled Image